Monetary policy and inequality - Asger Lau Andersen; Niels Johannesen; Mia Herløv Jørgensen; José-Luis Peydró (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2022)
We analyze the distributional effects of monetary policy on income, wealth and consumption. We use administrative household-level data covering the entire population in Denmark over the period 1987-2014 and exploit a long-standing currency peg as a source of exogenous variation in monetary policy. We consistently find that gains from softer monetary policy in terms of income, wealth and consumption are monotonically increasing in the ex-ante income level. The distributional effects reflect systematic differences in exposure to the various channels of monetary policy, especially non-labor channels (e.g. leverage and risky assets). Our estimates imply that softer monetary policy increases income inequality.
Keywords: E2; E4; E5; G1; G2; G5; 330; Monetary policy; Inequality; Household heterogeneity; Risky assets; Leverage